2002
DOI: 10.1021/jp020719o
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Gaseous Mercury with Atomic and Molecular Halogens:  Kinetics, Product Studies, and Atmospheric Implications

Abstract: Rapid depletions of atmospheric mercury (Hg 0 ) and ozone coinciding with high halogen concentrations have recently been observed in several high-Arctic and sub-Arctic regions. The lack of kinetic data on the halogen-initiated reactions of elemental mercury precluded the drawing of any conclusions on the chemistry of these mercury depletion events. We carried out extensive kinetic and product studies on the reactions of gaseous Hg 0 with molecular and atomic halogens (X/X2 where X = Cl, Br) at atmospheric pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
309
3
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 266 publications
(321 citation statements)
references
References 39 publications
8
309
3
1
Order By: Relevance
“…Recently, Sun et al [24] determined the rate coefficients using a relative rate technique with ethane and 2-chloro-propane as references. The rate coefficient for the Hg 0 + Cl• reaction was reported to be (1.8 ± 0.5) × 10 −11 cm 3 molecule −1 s −1 , at 100 kPa and 298 ± 3 K, which was in agreement with three earlier laboratory studies by Horne et al [27], Spicer et al [20] and Ariya et al [19] (1.0-6.4 × 10 −11 cm 3 molecule −1 s −1 ). However, the reported rate coefficient was about two orders of magnitude larger than that determined by Donohoue et al [28] (5.4 × 10 −13 cm 3 molecule −1 s −1 ) and one order of magnitude smaller than that determined by Byun et al [29] (1.2 × 10 −10 cm 3 molecule −1 s −1 ).…”
Section: Cl-initiated Oxidation Of Hgsupporting
confidence: 90%
See 3 more Smart Citations
“…Recently, Sun et al [24] determined the rate coefficients using a relative rate technique with ethane and 2-chloro-propane as references. The rate coefficient for the Hg 0 + Cl• reaction was reported to be (1.8 ± 0.5) × 10 −11 cm 3 molecule −1 s −1 , at 100 kPa and 298 ± 3 K, which was in agreement with three earlier laboratory studies by Horne et al [27], Spicer et al [20] and Ariya et al [19] (1.0-6.4 × 10 −11 cm 3 molecule −1 s −1 ). However, the reported rate coefficient was about two orders of magnitude larger than that determined by Donohoue et al [28] (5.4 × 10 −13 cm 3 molecule −1 s −1 ) and one order of magnitude smaller than that determined by Byun et al [29] (1.2 × 10 −10 cm 3 molecule −1 s −1 ).…”
Section: Cl-initiated Oxidation Of Hgsupporting
confidence: 90%
“…Measurements using a scanning mobility particle sizer by Sun et al [24] also showed that Hg products largely existed as wall deposits in agreement with the previous product analysis by Ariya et al [19]. It has been suggested that the presence of aerosols in the Aitken mode during the oxidation reaction may be initiated by the vapor nucleation of mercury-containing products.…”
Section: Br-initiated Oxidation Of Hgsupporting
confidence: 80%
See 2 more Smart Citations
“…Other theoretical [Khalizov et al, 2003;Goodsite et al, 2004] and experimental [Ariya et al, 2002] estimates of k 1 are faster (see Table 1), although Donohoue et al [2006] argue that these values are less accurate. The fastest k 1 value with reported temperature dependence [Khalizov et al, 2003] implies t global = 160 days, after recalculating k 2 to keep the k 1 :k 2 balance [Goodsite et al, 2004].…”
mentioning
confidence: 99%